2020
DOI: 10.1101/2020.09.05.250522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of Mcpip1 in Mcpip1AlbKOmice recapitulates the phenotype of human primary biliary cholangitis

Abstract: Background & Aims: Primary biliary cholangitis (PBC) is an autoimmune disease characterized by progressive destruction of the intrahepatic bile ducts. The immunopathology of PBC involves excessive inflammation; therefore, negative regulators of inflammatory response, such as Monocyte Chemoattractant Protein-1-Induced Protein-1 (MCPIP1, alias Regnase1) may play important roles in the development of PBC. The aim of this work was to verify whether Mcpip1 expression protects against development of PBC. Method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
(40 reference statements)
0
6
0
2
Order By: Relevance
“…Monocyte chemoattractant protein-induced protein 1 (MCPIP1, also known as Regnase-1) controls (post)transcriptionally the activation of inflammatory cells, for example by reducing the life of cytokines secreted by these cells. A recent study by Kotlinowski et al has demonstrated that loss of Mcpip1 in the liver (Mcpip1 fl/fl Alb Cre mouse model) increases the extent of inflammation and liver fibrosis and may be important in the pathogenesis of primary biliary cholangitis (Kotlinowski et al, 2021).…”
Section: Activation Of Hscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte chemoattractant protein-induced protein 1 (MCPIP1, also known as Regnase-1) controls (post)transcriptionally the activation of inflammatory cells, for example by reducing the life of cytokines secreted by these cells. A recent study by Kotlinowski et al has demonstrated that loss of Mcpip1 in the liver (Mcpip1 fl/fl Alb Cre mouse model) increases the extent of inflammation and liver fibrosis and may be important in the pathogenesis of primary biliary cholangitis (Kotlinowski et al, 2021).…”
Section: Activation Of Hscsmentioning
confidence: 99%
“…A recent study by Kotlinowski et al. has demonstrated that loss of Mcpip1 in the liver (Mcpip1 fl/fl Alb Cre mouse model) increases the extent of inflammation and liver fibrosis and may be important in the pathogenesis of primary biliary cholangitis (Kotlinowski et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, our observations are in accordance with another study, demonstrating that the deletion of Mcpip1 in Mcpip1 fl/fl Alb Cre mice is asymptomatic, in terms of blood morphology, cytokines, and chemokines detected in plasma. Instead, it leads to a massive hyperplasia of cholangiocytes and the development of primary biliary cholangitis [23]. The important role of Mcpip1 in regulation of hepatic homeostasis was recently demonstrated by Sun and coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…S3B-E). S4 right panel, asterisk) reflecting most of the features of human primary biliary cholangitis (PBC) (presented and discussed in details in [23]).…”
Section: Deletion Of Mcpip1 In Myeloid Cells But Not In Hepatocytes R...mentioning
confidence: 99%
“…Mcpip1 acts as an important regulator of liver homeostasis both in mice fed chow and mice fed a high-fat diet [8]. Additionally, its deletion in murine liver epithelial cells recapitulates the features of primary biliary cholangitis, which manifests as excessive proliferation of intrahepatic bile ducts, bile duct destruction, inflammatory infiltration and fibrosis [9]. Sun and coworkers described a protective role of Mcpip1 in liver recovery after ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%